The contribution of online content to the promotion and normalisation of female genital cosmetic surgery: A systematic review of the literature - Mowat, H.; McDonald, K.; Dobson, Amy; Fisher, J.; Kirkman, M. (Biomed Central Ltd., 2015)
Â© 2015 Mowat et al. Background: Women considering female genital cosmetic surgery (FGCS) are likely to use the internet as a key source of information during the decision-making process. The aim of this systematic review was to determine what is known about the role of the internet in the promotion and normalisation of female genital cosmetic surgery and to identify areas for future research. Methods: Eight social science, medical, and communication databases and Google Scholar were searched for peer-reviewed papers published in English. Results from all papers were analysed to identify recurring and unique themes. Results: Five papers met inclusion criteria. Three of the papers reported investigations of website content of FGCS providers, a fourth compared motivations for labiaplasty publicised on provider websites with those disclosed by women in online communities, and the fifth analysed visual depictions of female genitalia in online pornography. Analysis yielded five significant and interrelated patterns of representation, each functioning to promote and normalise the practice of FGCS: pathologisation of genital diversity; female genital appearance as important to wellbeing; characteristics of women's genitals are important for sex life; female body as degenerative and improvable through surgery; and FGCS as safe, easy, and effective. A significant gap was identified in the literature: the ways in which user-generated content might function to perpetuate, challenge, or subvert the normative discourses prevalent in online pornography and surgical websites. Conclusions: Further research is needed to contribute to knowledge of the role played by the internet in the promotion and normalisation of female genital cosmetic surgery.